2019
DOI: 10.1002/nop2.395
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the uptake of cervical cancer screening services in Tanzania: A health system perspective from national and district levels

Abstract: AimThis study aimed at examining factors influencing uptake of cervical cancer screening services among women in Tanzania.DesignExploratory qualitative study.MethodsIn‐depth interviews were used to obtain information from 10 key Informants. Of these, three were officials (policy makers) from the Reproductive Health‐Cancer Unit of Ministry of Health and Community Development, Gender, Elderly and Children (MoHCDGEC), three were health managers working at Kinondoni Municipal health system reproductive and child h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…Similarly, some authors identified that 30.4% of the respondents had not undergone cervical cancer screening because of fear of the screening procedure [26], which also significantly affected screening in this study. The findings from the study of [27] show that curative services were more prioritized over preventive services when the planning and allocation of resources from the national to the district level, which also affects utilization of preventive services even though not recognized in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, some authors identified that 30.4% of the respondents had not undergone cervical cancer screening because of fear of the screening procedure [26], which also significantly affected screening in this study. The findings from the study of [27] show that curative services were more prioritized over preventive services when the planning and allocation of resources from the national to the district level, which also affects utilization of preventive services even though not recognized in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Cervical cancer is not regarded as a priority disease and as such there is no budget to support implementation of activities related to prevention and controls. Other studies have reported lack of government funding and a high prevalence of NGO funding of cervical cancer programmes in Uganda, Kenya and Tanzania [41,58,59]. Through community advocacy, the participants of this study believed that cervical cancer would gain government attention and this will enable improvement in funding allocation to implement prevention and control services in the community.…”
Section: Discussionmentioning
confidence: 83%
“…This finding was consistent with the result of a study done in Dare Salam, which indicated that the national health system factors influencing the early uptake of cervical cancer screening services include poor flow of information from national to lower level. 23 …”
Section: Discussionmentioning
confidence: 99%